High time to enhance dancer welfare: a call to action to improve safeguarding and abuse prevention in dance - Cumming, Jennifer; Nordin-Bates, Sanna M.; Johnson, Carrie; Sanchez, Erin N.; Karageanes, Steven J. (BMJ Open Sport & Exercise Medicine, 2024)
While there is a lack of research into abuse in elite dance, numerous allegations of emotional, sexual and physical abuse of dancers can be found anecdotally in the media, legal convictions and personal accounts. As more dancers speak out, the scale of the problem within preprofessional schools and professional companies is becoming apparent. Accordingly, effective safeguarding mechanisms for preventing, identifying and reporting abuse are urgently needed. This viewpoint is intended to raise health professionals’ awareness of factors contributing to abusive practices found in dance environments and the potential clinical implications of abuse to dancers’ health and well-being. We also call for research and policy engagement on safeguarding and abuse prevention designed and implemented in partnership with stakeholders, aiming to promote safe and positive dance environments for all.